Cost Considerations For Reinforced Concrete Office Building In Malaysia Incorporating Seismic Design - Lim, Yi Ping, Eveline (Universiti Sains Malaysia, 2021)
Malaysia is a developing country with new buildings being constructed rapidly in its major cities. As such, the seismic design must be considered to overcome possible earthquake hazards. Most of the office buildings in Malaysia are designed with gravity load considerations but not incorporating seismic design, referring to Eurocode 8. This study is carried out with the aim to evaluate the effect of considering seismic load towards the material demand for the structural frame and the overall cost compared to non-seismic load. Models with 10-storey, 15-storey, 20-storey, 25-storey, and 30-storey were designed using ETABS software. The buildings were designed using EC 2 and MS 1553:2002 when subjected to gravity load and wind load. On the other hand, EC 8 and Malaysia National Annex were used for seismic considerations. The selected reference PGA values were 0.05g, 0.10g, and 0.165g as it represents the seismicity conditions that are found in Peninsular, Sarawak, and Sabah, respectively. In general, the results showed that building models incorporating seismic design resulted in increments in concrete and reinforcement demand compared to conventional design. However, the percentage of increments in the material demand varied with the type of structural frame elements. Moreover, the total material cost when comparing seismic with non-seismic design was in the range of 10% - 67% and -4% - 60% for medium and high-rise buildings, respectively. This finding is because the wind load acting on high-rise buildings becomes more critical and particularly true for low seismicity level (0.05g). It can be concluded that, when the high-rise buildings are subjected to wind load, the total material cost will be higher when compared to seismic design adopting the low PGA level.